Powder recycling for electron beam powder bed fusion of TiAl alloy - Feihong Wang; Mengchen Song; Yongfeng Liang; Gengwu Ge; Xiaoyu Liang; Feng Lin; Honghui Wu; Dongfang Wang; Wenbin Kan; Li Liu; Junpin Lin (Materials & Design)
This study systematically investigates the impact of powder recycling (up to 70 cycles) on Ti-48Al-2Cr-2Nb (at.%) alloy processed by electron beam powder bed fusion (EB-PBF). Comprehensive characterization (SEM/XRD/EBSD/XPS) reveals three key phenomena of recycling powder: (1) progressive Al depletion (48.43 → 46.31 at.%) and oxygen uptake (560 → 2000 ppm) at 22–28 ppm/cycle, (2) phase evolution from α/α2 to γ + B2 with C14 Laves phase precipitation (>30 cycles), and (3) surface oxide transformation from TiO2/Al2O3 (54 %:46 %) to Al2O3-dominated (82 %). The changes in these powders will affect the room temperature ultimate tensile strength (750 MPa) and ductility (reduced by 40 %) of the formed workpiece through grain refinement (≤ 10 μm) and other means. The phase transformations of powders and parts are attributed to thermal exposure at 900–1150 °C, with Cr segregation driving Laves phase formation. While oxide modification improves powder flowability, the increase of irregular powder increases part surface roughness. Quantitative analysis demonstrates that maintaining 15–30 % fresh powder optimizes the cost-performance ratio, providing practical guidelines for industrial implementation. These findings advance the understanding of powder degradation mechanisms in EB-PBF and establish scientifically-grounded limits for TiAl alloy powder reuse in critical aerospace applications.